Effects of US quantitative easing on emerging market economies - Saroj Bhattarai; Arpita Chatterjee; Woong-yong Park (Asian Development Bank Institute (ADBI), 2018)
We estimate international spillover effects of US Quantitative Easing (QE) on emerging market economies (EMEs). Using a Bayesian VAR on monthly US macroeconomic and financial data, we first identify the US QE shock. The identified US QE shock is then used in a monthly Bayesian panel VAR for EMEs to infer spillover effects on these countries. We find that an expansionary US QE shock has significant effects on financial variables in EMEs. It leads to an exchange rate appreciation, a reduction in long-term bond yields, a stock market boom, and an increase in capital inflows to these countries. These effects on financial variables are stronger for the "Fragile Five" countries compared to other EMEs.
Keywords: C31; E44; E52; E58; F32; F41; F42; 330; US quantitative easing; spillovers; emerging market economies; Bayesian VAR; panel VAR; fragile five countries